Bismuth quadruple regimen with tetracycline or doxycycline versus three‐in‐one single capsule as third‐line rescue therapy for Helicobacter pylori infection: Spanish data of the European Helicobacter pylori Registry (Hp‐EuReg). Issue 5 (13th July 2020) - Nyssen, Olga P.; Perez‐Aisa, Angeles; Rodrigo, Luis; Castro, Manuel; Mata Romero, Pilar; Ortuño, Juan; Barrio, Jesus; Huguet, Jose Maria; Modollel, Ines; Alcaide, Noelia; Lucendo, Alfredo; Calvet, Xavier; et al.
Abstract: Background: Different bismuth quadruple therapies containing proton‐pump inhibitors, bismuth salts, metronidazole, and a tetracycline have been recommended as third‐line Helicobacter pylori eradication treatment after failure with clarithromycin and levofloxacin. Aim: To evaluate the efficacy and safety of third‐line treatments with bismuth, metronidazole, and either tetracycline or doxycycline. Methods: Sub‐study with Spanish data of the "European Registry on H pylori Management" (Hp‐EuReg), international multicenter prospective non‐interventional Registry of the routine clinical practice of gastroenterologists. After previous failure with clarithromycin‐ and levofloxacin‐containing therapies, patients receiving a third‐line regimen with 10/14‐day bismuth salts, metronidazole, and either tetracycline (BQT‐Tet) or doxycycline (BQT‐Dox), or single capsule (BQT‐three‐in‐one) were included. Data were registered at AEG‐REDCap database. Univariate and multivariate analyses were performed. Results: Four‐hundred and fifty‐four patients have been treated so far: 85 with BQT‐Tet, 94 with BQT‐Dox, and 275 with BQT‐three‐in‐one. Average age was 53 years, 68% were women. Overall modified intention‐to‐treat and per‐protocol eradication rates were 81% (BQT‐Dox: 65%, BQT‐Tet: 76%, BQT‐three‐in‐one: 88%) and 82% (BQT‐Dox: 66%, BQT‐Tet: 77%, BQT‐three‐in‐one: 88%), respectively. By logistic regression, higher eradication rates were associated with compliance (OR = 2.96; 95% CI = 1.01‐8.84) and no prior metronidazole use (OR = 1.96; 95% CI = 1.15‐3.33); BQT‐three‐in‐one was superior to BQT‐Dox (OR = 4.46; 95% CI = 2.51‐8.27), and BQT‐Tet was marginally superior to BQT‐Dox (OR = 1.67; 95% CI = 0.85‐3.29). Conclusion: Third‐line H pylori eradication with bismuth quadruple treatment (after failure with clarithromycin and levofloxacin) offers acceptable efficacy and safety. Highest efficacy was found in compliant patients and those taking 10‐day BQT‐three‐in‐one or 14‐day BQT‐Tet. Doxycycline seems to be less effective and therefore should not be recommended.